Perilaku Komunikasi Komunitas Kpopers Palangka Raya dalam Loyalitas pada Idola - Tirra Nugrahani Dewi; Nurudin (Jurnal Komunikasi Nusantara, 2022)
The Kpopers community is a separate communication behavior for young people in the midst of social life, because its unique lifestyle makes this community exist and be known in Palangka Raya City. Some of the ways that this community does to exist is by imitating the way they dress and covering dance movements of their idol boy groups and girl groups, as well as K-Pop music fans who experience technological advances that can facilitate the spread of popular culture, causing consumptive behavior on matters related to his idol. This study aims to determine the motives of members to join the Kpopers community in Palangka Raya, the meaning of Korean Pop (Kpop) for members of the Palangka Raya Kpopers community and the communication experiences of members of the Kpopers community in Palangka Raya. A qualitative approach is used in this research. Data collection is carried out through in-depth interviews, observation and study of documentation and literature. Communication is carried out through various activities, including festival events and publications. The message, which is designed in such a way as to be channeled through various media, is a strategic step to introduce and share the latest information on their idols so that they are widely known by the public so that efforts to increase their idol branding and promotion can take place continuously. Abstrak Komunitas Kpopers merupakan perilaku komunikasi tersendiri bagi kaum muda di tengah kehidupan sosial, karena gaya hidupnya yang unik membuat komunitas ini eksis dan dikenal di Kota Palangka Raya. Beberapa cara yang dilakukan komunitas ini untuk tetap eksis adalah dengan meniru cara mereka berpakaian dan meliput gerakan dance boy group idola dan girl group mereka, serta para penggemar musik K-Pop yang mengalami kemajuan teknologi yang dapat memfasilitasi penyebaran budaya populer, menyebabkan perilaku konsumtif pada hal-hal yang berhubungan dengan idolanya. Tujuan dari penelitian ini adalah untuk mengetahui motivasi anggota bergabung dalam komunitas Kpopers Palangkaraya, apa makna musik K-pop (Kpop) bagi anggota komunitas Kpopers Palangkaraya, dan pengalaman komunikasi anggota komunitas Kpopers Palangkaraya. Penelitian ini menggunakan metode kualitatif. Pengumpulan data dilakukan melalui observasi, wawancara, penelitian kepustakaan, dan penelitian kepustakaan. Komunikasi dilakukan melalui berbagai acara, termasuk festival dan publikasi. Informasi yang dirancang untuk disebarluaskan melalui berbagai media merupakan langkah strategis untuk menyajikan dan berbagi informasi terbaru tentang idola agar publik dapat mengetahuinya secara luas, guna berupaya meningkatkan brand mereka. Promosi dapat dilakukan secara berkelanjutan.